Uso de tres tipos de suelo y su efecto en la resistencia a la compresión de adobe mejorado. Zungarococha Iquitos.2022 - Huatatuca Collins, Janz Peter (2023)
The research evaluated the compressive strength of artisanal adobe with three types of soil: loamy soil, clayey loamy soil and silty loamy soil with an addition of 30% rice husk according to volume, to measure its priority and benefit as well as the disadvantages of the final product. The hypothesis is that at least one of the types of soil with the incorporation of rice husks improves its mechanical resistance to adobe compression in Kg/cm2. The earth was extracted from different places in the community of Puerto Almendras, Nina Rumi, from the National University of the Peruvian Amazon. A total of 24 compacted samples were made with 30% addition of rice husk according to volume. The compressive strength test of the adobe samples was carried out in the soil laboratory on quality control of materials and pavements of the Loreto Regional Directorate of Transport and Communications, in which the following results were obtained: loam soil clayey with a compressive strength of 25.11 kg/cm2; loam soil with an average compressive strength of 24.39 Kg/cm2; silt loam soil with a compressive strength of 24.2 Kg/cm2.